Perlindungan Hukum kepada Pekerja yang Terkena PHK Akibat dari Pandemi Covid–19 - Adijoyo Susilo Kusumaweningrat (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Employment relations do not always run smoothly so as to allow disputes between workers and employers in terms of Termination of Employment. An interesting phenomenon to be discussed regarding Termination of Employment in this study, namely due to the Covid-19 Pandemi. Indonesia anticipates this by issuing policies regulated in Government Regulation no. 21 of 2020 concerning PSBB, which aims to break the chain of the spread of Covid-19. This study aims to determine the Covid-19 Pandemi which was used as a reason for Termination of Employment in terms of Law No. 11 of 2020 concerning Job Creation and to find out the Responsibilities of Hospitality Companies in Garut Regency related to Law No. 13 of 2003 concerning Employment, This research method is normative juridical using analytical descriptive research specifications. This data collection technique is through literature study using secondary data sources consisting of primary, secondary and tertiary legal materials. This data analysis method is a systematic interpretation method. Based on the results of the study, it is known that the Termination of Employment during the Covid-19 pandemi that occurred in Hospitality in Garut Regency was based on insufficient hotel operational costs and the responsibility carried out by the company for workers was to provide wages that were adjusted to applicable regulations. Abstrak. Hubungan kerja tidak selalu berjalan dengan lancar sehingga memungkinkan adanya perselisihan antara pekerja dan pengusaha dalam hal PHK. Fenomena yang menarik untuk dibahas terkait PHK dalam penelitian ini, yaitu akibat adanya Pandemi Covid-19. Indonesia mengantisipasinya dengan mengeluarkan kebijakan yang diatur dalam PP No. 21 Tahun 2020 tentang PSBB, yang bertujuan untuk memutus rantai penyebaran Covid-19. Penelitian ini bertujuan untuk mengetahui Pandemi Covid-19 yang dijadikan alasan untuk PHK ditinjau dari UU 11 Tahun 2020 tentang Cipta Kerja dan untuk mengatahui Tanggung Jawab Perusahaan Perhotelan di Kabupaten Garut dihubungkan dengan UU No 13 Tahun 2003 tentang Ketenagakerjaan, Metode Penelitian ini adalah yuridis normative dengan menggunakan spesifikasi penelitian deskritif analitis. Teknik pengumpulan data ini melalui studik kepustakaan dengan menggunakan sumber data sekunder yang terdiri dari bahan hukum primer,sekunder dan tersier. Metode analitis data ini adalah metode penafsiran sistematis. Berdasarkan hasil penelitian diketahui bahwa PHK pada masa pandemi Covid-19 yang terjadi di Perhotelan di kabupaten garut berdasarkan tidak tercukupinya biaya operasional hotel dan Tanggung Jawab yang dilakukan oleh perusahaan terhadap para pekerja adalah dengan memberi upah yang di sesuaikan dengan peraturan yang berlaku.